Effect of Parboiling Treatment on the Milling Quality of Selected Rice Varieties - Ayalew, Zewdu; Fanta, Abebe; Abera, Solomon (Journal of Postharvest Technology, 2013)
Based on previous results indicating excessive milling loss inherent in rice milling process in Ethiopia, a study was conducted to evaluate the effects of parboiling treatment on three released (Gumara, Kokit, and Tigabe) and one local (X-Jigna) rice varieties. Parboiled and un-parboiled rice samples were milled using small and portable Rice Whitener (SRW). The result has indicated that the response for Parboiling is variety specific. But, in general, parboiling resulted in improved milling quality in most of the studied varieties. An overall increase in Milling yield (from 62.70 to 65.83%), milling recovery (from 79.50 to 83.97%) and whole grain yield (from 27.83 to 37.68%), was observed while milling loss has reduced (from 16.50 to 12.50%) by this treatment. Likewise, parboiling reduced machine throughput and output. Milling qualities of Gumara and Tigabe and, to some extent, Kokit varieties had been improver and that of X-Jigna declined when milled parboiled. Tigabe and Kokit had shown more or less similar milling properties when milled raw but Tigabe had shown better milling qualities when milled after parboiling. Thus, from the overall results of the research it become clear that milling qualities of the three varieties (Gumara, Tigabe,and Kokit) can be improved by parboiling. But parboiling had undesirable consequences on milling qualities of X-Jigna variety. It is therefore recommended that, along with improving the design of SRW machine, use of parboiling for selected varieties should be encouraged. Besides, under raw paddy milling conditions varieties with better milling quality as X-Jigna should preferably be promoted than lower milling quality Gumara variety. Improving the milling quality of Gumara and Tigabe by parboiling may also be useful.